EARLY NEUROPSYCHOLOGICAL DIAGNOSIS AND INTERVENTION IN CHILDREN AT GENETIC RISK BORN FROM CONSANGUINEOUS MARRIAGES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The issue of early diagnosis and intervention in the neuropsychological development of children born from consanguineous marriages is an urgent topic in clinical neuropsychology and child psychiatry. High genetic burden associated with consanguinity increases the risk of primary and secondary developmental delays. Typical deviations include delayed speech, reduced cognitive development, executive dysfunction, and behavioral and emotional instability.
Keywords: Neuropsychological diagnosis, genetic risk, consanguinity, preschool children, cognitive intervention, early intervention.